Functional neurosurgery And Neuro-cognitive Rehabilitation - Zarghi, Afsaneh (International Clinical Neuroscience Journal, 2014)
Cognitive rehabilitation is a group of designed techniques that is for the promotion of cognitive domains in people with disease or disability. Cognitive rehabilitation therapy (CRT) is the science of restoring cognitive processing and learning compensatory strategies and it affects the molecular and cellular recovery rehabilitation by integration of behavioral and cognitive changes. The promotion of rehabilitation science of cognitive neuroscience has made it a priority by the help of full range of effected interventional procedures. It has been able to achieve the desired goals in the chain of theoretical and experimental science on the basis of behavioral interventions which is made of neuroscience, cognitive neuroscience, psychology, physiology, pharmacology, medical imaging, and other medical disciplines and achieved some success in compensatory and medical strategies after surgery. Cognitive impairment after brain surgery is huge health challenges beyond the common disorders associated with diseases. Our approach to CRT is on the assumption that treatment would be the most effective way when focusing on the cognitive sub-systems after neurosurgery and these are also affected by other aspects of life as a patient emotions, nutrition, health, stress, and social performance. Intervention in the passive skills can lead to neuro-cognitive rehabilitation that includes designed experience on the basis of nerve and brain function and structure. A failure of cognitive or brain processing during or after surgery is an abnormal result and these impairments are treated better with CRT. This method is on the basis of neuroplastisity, reorganization of damaged cortical through morphological and physiological responses of nerve reconstruction ways by techniques in neuro-cognitive disorders due to illness, injury or disability, even in healthy individuals which are affected by environment, the complexity of stimulation, repeated tasks and motivation.